2019
DOI: 10.1177/1363459318785681
|View full text |Cite
|
Sign up to set email alerts
|

Improving rural public health through ‘best practice’ water, sanitation and hygiene initiatives

Abstract: An understanding of best practice rural water, sanitation and hygiene (rWASH) and its associated indicators can ensure greater success and reduced failure of future projects. While numerous organisations have actively implemented rWASH projects since the early 1990s with donor reports, funding proposals and reviews frequently claiming best practice, there remains a paucity of information on what constitutes 'best practice' rWASH. A scoping review of qualitative and quantitative literature was done with six pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The 2030 Agenda proposes 169 targets to be achieved globally through 17 sustainable development goals (SDGs), so that societies are able to respond to the current situation. Sustainable water management is related to various SDGs, among which it is worth highlighting global access to food and the eradication of hunger (SDG 2) [11][12][13]16,28], good health and well-being (SDG 3) [8,9,11,13,15,17,18,22,26,[41][42][43][44][45][46][47][48][49][50], quality education (SDG 4) [32,33,38,39], clean water and sanitation (SDG 6) [7,[13][14][15]27,[42][43][44]46,47,51], sustainable cities and communities (SDG 11) [6,8,12,13,17,[26][27][28]…”
Section: Introductionmentioning
confidence: 99%
“…The 2030 Agenda proposes 169 targets to be achieved globally through 17 sustainable development goals (SDGs), so that societies are able to respond to the current situation. Sustainable water management is related to various SDGs, among which it is worth highlighting global access to food and the eradication of hunger (SDG 2) [11][12][13]16,28], good health and well-being (SDG 3) [8,9,11,13,15,17,18,22,26,[41][42][43][44][45][46][47][48][49][50], quality education (SDG 4) [32,33,38,39], clean water and sanitation (SDG 6) [7,[13][14][15]27,[42][43][44]46,47,51], sustainable cities and communities (SDG 11) [6,8,12,13,17,[26][27][28]…”
Section: Introductionmentioning
confidence: 99%
“…If we aim to attain the universal health coverage, WASH is an essential and integral component, and the present status depicts an unacceptable health risk exposing millions of people to an unhealthy and unsafe world 2 . In order to improve the existing scenario, a series of steps have been proposed with an aim to formulate national plans, set targets, upgrade infrastructure and involve local communities 3,4 . The first and foremost step is to perform a situation analysis (pertaining to existing policies, financial support, etc.)…”
mentioning
confidence: 99%
“…Further, it has been concluded that the WASH services are below standard in all the regions of the world 1 . Moreover, it is important to note that such circumstances not only enhances the incidence of infections, caseload, burden on the health system, but also is a crucial factor for the rise in the number of multi-drug resistant infections and even compromises the safety and dignity of the patients [1][2][3] . There are no second thoughts that a child born in a health facility with poor WASH standards is at immense risk of acquiring the Infection & death, and the same applies to the mother as well 2,3 .…”
mentioning
confidence: 99%
See 2 more Smart Citations